MANAJEMEN EKSTRAKURIKULER DALAM PENGUATAN KARAKTER PESERTA DIDIK DI SD SAINS ISLAM AL FARABI - Nurkholis Nurkholis; Maftuhah Dewi (PGSD Universitas Muhammadiyah Cirebon, 2022)
Education is one of the main needs of a person to develop self-potential, intelligence and skills and strengthen the character and personality of students. With education, it is hoped that someone can dig up information or knowledge, train every talent they have to be of higher quality and develop the character and personality of students. Competence skills that support good behavior will produce good and competitive HR products in the future The purpose of this research is more on the management of extracurricular activities. First, study extracurricular programs and activities, second forms of extracurricular activities, thirdly the technical implementation of extracurricular activities and finally parental support in extracurricular activities. This study uses descriptive analysis method with a qualitative approach and data collection techniques through observation, interviews and documentation. Compulsory extracurricular activities include Scouts, BPI, and Calistung. Extracurricular activities include Archery, Angklung, Futsal and English Fun. Extracurricular itself plays an important role in strengthening the quality of discipline of SDSI Al Farabi students. Technically, SDSI Al Farabi's extracurricular activities are responsible for the student sector. Parents of students support all activities related to extracurricular activities, as evidenced by the attitude of parents in guiding their children in practice and guiding students to take part in competitions. Keywords: Extracurricular Management, Character Strengthening